2018
DOI: 10.1111/exd.13526
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 expression by tumor cell lines: A predictive marker in melanoma

Abstract: Prognostic biomarkers for patients with melanoma after lymph node resection are of clinical relevance and could thus enable the identification of patients who therefore would most benefit from adjuvant treatment. The aim of this work was to determine, using an in vitro model, whether immune-related biomarkers, such as MHC-class I and II, melanoma-associated antigens, IDO1 and PD-L1, could also be relevant to predict the risk of relapse of patients with stage III melanoma after lymph node resection. We establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…This in vivo observation can be reenacted by exposing tumor cells to IFN-ɣ, thereby leading to a marked increase of PD-L1 expression (Knol et al [62] and Fig. 3a).…”
Section: Discussionmentioning
confidence: 86%
“…This in vivo observation can be reenacted by exposing tumor cells to IFN-ɣ, thereby leading to a marked increase of PD-L1 expression (Knol et al [62] and Fig. 3a).…”
Section: Discussionmentioning
confidence: 86%
“…To investigate this hypothesis we used the model of co-culture of a melanoma cell-line and autologous TILs obtained from the same patient (6), with the addition of IDO inhibitor. The endpoints were the frequency of reactive autologous T cells among the TILs and the expression of molecules involved in the recognition of tumour antigens by T cells with and without IDO inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…Tryptophan deficiency inhibits the activity and proliferation of T cells (5). A recent paper (6) has shown that IDO1 expression in metastatic melanoma lymph nodes is associated with an increased risk of relapse and death. Thus, we hypothesize that the presence of IDO in the tumour microenvironment could inhibit the activity of TILs, and that adding an IDO inhibitor to the TILs could increase their cytotoxic activity against melanoma cells.…”
mentioning
confidence: 99%
“…One obstacle is defined by the insufficient migration of CAR‐T cells from the blood vessels to the tumor site, which is necessary for effective tumor eradication . Once entered, CAR‐T cells need to struggle through the unfavourable tumor microenvironment (TME) in order to induce a potent anti‐tumor immune response . Finally, the selection of the optimal target antigen is an important step, as T cells should be equipped with a CAR recognizing an antigen that is exclusively expressed on cancer cells rather than on healthy tissue to prevent on‐target/off‐tumor toxicities .…”
Section: Introductionmentioning
confidence: 99%